A more ecological and efficient approach for producing diosgenin from Dioscorea zingiberensis tubers via pressurized biphase acid hydrolysis. (10th September 2016) - Yang, Huan; Yin, Huawu; Shen, Yuping; Xia, Guohua; Zhang, Bo; Wu, Xiangyang; Cai, Baochang; Tam, James P.
Abstract: Diosgenin (CAS No.: 512-04-9) hydrolyzed from Dioscorea zingiberensis C. H. Wright is a very important steroid in the pharmaceutical industry. However, serious environmental pollution and poor efficiency in the utilization of this natural resource have yet to be conquered. The aim of this study was to establish a more ecological and efficient approach for producing diosgenin from fresh D. zingiberensis tubers via pressurized biphase acid hydrolysis after recycling the cellulose and starch. The reaction was carried out in a high pressure kettle, and seven parameters, including the sample to acidic solution ratio, concentration of H2 SO4 aqueous solution, volume of extraction solvent, reaction temperature, duration of hydrolysis, agitation speed and boiling point of petroleum ether, were sequentially optimized through single factor experimental design. It was shown that the yield of diosgenin has been increased to 4.17% under the optimal conditions, namely, a 1:100 ratio of saponin/acidic solution (g/mL), 50 mL of 2 μL/mL H2 SO4 aqueous solution, 30 mL of petroleum ether (90–120 °C), 130 °C, 2.0 h and 100 r/min. Then, the newly proposed approach was compared with our previous strategy as well as a conventional method in terms of the yield of diosgenin, the consumption of sulfuric acid and chemical oxygen demand as well as total organic carbon of wastewater. Consequently, it was found that the yield was 22.29% higher than the conventional process, and H2 SO4 consumption was reduced by 88.53%. Furthermore, the level of pollution in wastewater of the novel strategy has fallen greatly as the chemical oxygen demand and the total organic carbon were decreased by 50.15% and 64.39%. Comprehensively, it has been well-demonstrated that the novel strategy based on pressurized biphase acid hydrolysis after recycling the cellulose and starch is a more ecological and effective approach for producing diosgenin from the tubers of fresh D. zingiberensis, and it is a promising strategy for application in industrial practice. Graphical abstract: Highlights: The yield of diosgenin was increased by 22.29%. The consumption of sulfuric acid was reduced by 88.53%. Recycled cellulose and starch can be further utilized and not cause severe pollution. The level of pollution in wastewater has fallen significantly. The newly proposed strategy was promising for application in industrial practice.